Potential for Extrinsic Incubation Temperature to Alter Interplay between Transmission Potential and Mortality of Dengue-Infected - Rebecca C. Christofferson; Christopher N. Mores (Environmental Health Insights, 2016)
The extrinsic incubation period is a critical component in the assessment of arboviral transmission potential. It defines the time it takes for a mosquito to become infectious following exposure to an arbovirus. Since this is a temporal process, the lifespan of a mosquito is intimately tied to the extrinsic incubation period and thus transmission potential of these viruses. Temperature is a known effector of both vector competence (the ability of a vector to transmit a pathogen) and mosquito mortality, but the interaction among temperature, vector competence, and mosquito mortality is not well characterized. Herein, we investigate this interaction for dengue virus, serotype 2, and its primary vector Aedes aegypti where we found that at 30 ° C, infection and/or dissemination shortened the average lifespan of the mosquito and that when considering only mosquitoes with a disseminated infection, those incubated at 26 ° C lived significantly longer.